Research on differential Pattern time delay shift coding underwater acoustic communication - Jing-wei YIN; Xiao ZHANG; Xue-li SHENG; Chao SUN (Tongxin xuebao)
A differential Pattern time delay shift coding(DPDS)method with a non-fixed code width based on the traditional Pattern time delay shift coding was proposed.The information is carried by the time delay between adjacent code element,the different linear frequency modulation(LFM)signal is used for adjacent code division.The DPDS system has an ability anti inter-symbol interference(ISI)and the Doppler effects.The computer simulation and lake tests prove that the DPDS system can improve the communication rate,inhibit the ISI caused by the multi-path channel and anti the Doppler effects.It is proved that the system has an effectiveness and robustness.